Effect of the sanitation, hygiene, information, and education intervention on WaSH practices and related health outcomes among children in rural Anganwadi centres: a non-randomised cluster trial pilot tested in Odisha, India - Kar, Sonali; Singh, Snigdha; Ray, Angana; Pattnaik, Baishnabi; Das, Sumelika; Das, Ayesha; Nayak, Rosy (Frontiers in Public Health, 2025)
BackgroundInadequate water, sanitation, and hygiene (WaSH) facilities in Anganwadi centres, critical components of India’s Integrated Child Development Services (ICDS), adversely affect child health. The SHINE (Sanitation, Hygiene, Information, and Education) intervention aimed to improve WaSH practices and related health outcomes in rural Anganwadis of Odisha.MethodsThis was a quasi-experimental, non-randomised cluster study conducted between April and October 2024 across four Anganwadi centres under the Rural Health Training Centre (RHTC), Kalinga Institute of Medical Sciences (KIMS), Odisha. Clusters were defined geographically: centres within 5 km of RHTC were assigned to the intervention arm, while those beyond 5 km served as controls. This distance criterion was selected to reduce the contamination risk of the intervention. Due to the nature of the intervention, blinding was not feasible.ResultsForty-five children were enrolled (intervention: 23 and control: 22). The intervention group showed significant improvements in safe drinking water usage (from 0 to 60.9%, AOR = 6.88), footwear use in toilets (17.4 to 78.3%, AOR = 5.18), and handwashing before meals (0 to 82.6%, AOR = 6.85). Infection symptoms declined markedly (from 39.1 to 4.4%, AOR = 5.18). Improvements in food hygiene and school infrastructure were observed. Absenteeism decreased, but not significantly. Control schools showed modest improvements, possibly due to the Hawthorne effect.ConclusionThe SHINE intervention significantly improved WaSH practices and reduced illness among Anganwadi children. The findings support integrating behaviour-centred WaSH interventions into early childhood education programs to promote health and reduce preventable disease in low-resource settings.